The Development Of Axiological Thoughts In Our National Pedagogy - Shonazarova Sevara Rashidovna (Global Scientific Publishing, 2025)
This article discusses the formation of philosophical concepts in students based on an axiological approach in our national pedagogy, the presence of a philosophical worldview in students' consciousness, the process related to the individual's assimilation of cultural values, the clear manifestation of axiological consciousness in various aspects, the axiological form of worldview, and axiological thoughts.
Keywords: Axiological approach; traditional education